Age-Related Developmental and Individual Differences in the Influence of Social and Non-social Distractors on Cognitive Performance - Tan, Patricia Z.; Silk, Jennifer S.; Dahl, Ronald E.; Kronhaus, Dina; Ladouceur, Cecile D. (Frontiers in Psychology, 2018)
This study sought to examine age-related differences in the influences of social (neutral, emotional faces) and non-social/non-emotional (shapes) distractor stimuli in children, adolescents, and adults. To assess the degree to which distractor, or task-irrelevant, stimuli of varying social and emotional salience interfere with cognitive performance, children (N = 12; 8-12y), adolescents (N = 17; 13-17y), and adults (N = 17; 18-52y) completed the Emotional Identification and Dynamic Faces (EIDF) task. This task included three types of dynamically-changing distractors: 1) neutral-social (neutral face changing into another face); 2) emotional-social (face changing from 0% emotional to 100% emotional); and 3) non-social/non-emotional (shapes changing from small to large) to index the influence of task-irrelevant social and emotional information on cognition. Results yielded no age-related differences in accuracy but showed an age-related linear reduction in correct reaction times across distractor conditions. An age-related effect in interference was observed, such that children and adults showed slower response times on correct trials with socially-salient distractors; whereas adolescents exhibited faster responses on trials with distractors that included faces rather than shapes. A secondary study goal was to explore individual differences in cognitive interference. Results suggested that regardless of age, low trait anxiety and high effortful control were associated with interference to angry faces. Implications for developmental differences in affective processing, notably the importance of considering the contexts in which purportedly irrelevant social and emotional information might impair, vs improve cognitive control, are discussed.